The effects of community-based exercise modalities and volume on musculoskeletal health and functions in elderly people - Lim, Chin Leong; Keong, Nicholas Ling Swee; Yap, Margaret Mei Chan; Tan, Alvin Wai Kit; Tan, Cher Heng; Lim, Wee Shiong (Frontiers in Physiology, 2023)
The effects of different muscle loading exercise (MLEX) modes and volume on musculoskeletal health is not well-studied in older populations. Aim: Therefore, this study aimed to compare the effects community-based MLEX modalities and volume on musculoskeletal health in elderly people. Methods: Elderly men (n=86) and women (n=170), age 50 – 82 years old were assigned to the sedentary (SE, n=60), muscle strengthening exercise (MSE, n=71), aerobic exercise (AE, n=62) and Tai Chi exercise (TCE, n=63) groups, based on > 2 years of exercise history. Exercise volume was compared between “Minimum” (“Min” < 60 min/week), “Low” (60 – 120 min/week). “Moderate” (121 – 239 min/week) and “High” (240 – 720 min/week) volumes. Results: All three modes of MLEX were associated with lower percentage of body fat (BF%) and higher percentage of lean body mass (LBM%, p = 0.003 main effect of group, and p = 0.002 main effect of volume for both BF% and LBM%), but not with higher bone mineral density (BMD, total body, lumbar spine, total hip and neck of femur), than SE. TCE had a distinct advantage in trunk flexibility (p = 0.007 with MSE, p = 0.02 with AE, and p = 0.01 with SE), and both TCE (p = 0.03) and AE (p = 0.03) performed better than SE in the one-leg stand balance test. Isometric strength and throwing speed and peak power with a 2 kg power ball were higher in the MLEX than SE groups (p = 0.01), in the ranking order of MSE, AE and TCE. However, there was no difference in handgrip strength performance between the MLEX groups, which performed better than the SE participants. Accumulating > 120 min/week of MLEX can promote body composition health and muscle functions, but 60 min/week of MSE alone may have equal or better outcomes in these parameters. Conclusion: Community-based MLEX classes may be used to mitigate the age-related chronic disease that are associated with body composition and muscular functions.